Gingivitis: The Contributing Roles of Dentist, Nursing, and Medical Documentation System-An Updated Review - Alfahmi , Saadah Hameed Mohammed; Almaliky, Afnan Abdullah; Mandeel, Amal Mohammed Ibn; Aldossari , Waad Saad; Albishi , Noura Ali; Albishi, Mona Ali; Albishi , Thara Ali; Albishi, Sarra Ali; Aljohani , Sarah Ayedh; Alkhelb, Alia Abdulaziz (Journal of Ecohumanism, 2024)
Background: Gingivitis is an inflammatory condition affecting the gingival tissues, primarily caused by microbial plaque accumulation, and is the most prevalent periodontal disease. It is characterized by gingival redness, swelling, and bleeding, although it is often asymptomatic in its early stages. The disease is classified into several forms, with plaque-induced gingivitis being the most common. Aim: The purpose of this review is to examine the roles of dentists, nurses, and medical documentation systems in the management and prevention of gingivitis, with a focus on effective interventions and clinical outcomes. Methods: A comprehensive review of the literature was conducted to evaluate the etiology, pathophysiology, clinical presentation, and treatment of gingivitis. The roles of healthcare providers, including dental professionals and nursing staff, in managing the disease were analyzed, along with the significance of accurate medical documentation systems in patient care. Results: Gingivitis is primarily caused by bacterial plaque, although nutritional deficiencies, hormonal changes, and drug use can also contribute. Management typically involves mechanical plaque removal, oral hygiene education, and professional scaling. Nurses and dentists work collaboratively to assess symptoms, educate patients, and monitor progress. Medical documentation systems play a critical role in tracking patient history, treatment plans, and outcomes. Conclusion: Gingivitis can be effectively managed through early intervention, proper oral hygiene, and regular dental visits. Accurate medical documentation is essential for tracking the disease's progression and ensuring appropriate treatment. The combined efforts of dentists, nursing staff, and robust documentation systems are crucial in improving patient outcomes and preventing complications.